Respuesta :

Answer:

2x^{2} + 2x - 56 = x^{2} + x\\

x_1 = -8    

x_2 = 7

x^{2} -9x= x- 9\\

x_1  = 1

x_2 = 9

Step-by-step explanation:

 

2x^{2} + 2x - 56 = x^{2} + x\\

2x^{2} + 2x - 56 - x^{2} - x\\

x^{2} + x - 56 = 0\\

x_1,2  =  (-b ± √(b^2-4 ac))/2a

                                                                       a = 1, b = 1, c = -56

                                                                   

x_1,2  =  (-1 ± √(1^2-4*1* (-56)))/(2*1)

   

x_1  =  (-1- √(1^2-4*1* (-56)))/(2*1)

   

x_1  =  (-1- √(1^2-4*1* (-56)))/(2*1)= -8

   

x_2  =  (-1+ √(1^2-4*1* (-56)))/(2*1)= 7

Proof

2*(-8)^{2} + 2*(-8)- 56 =(-〖8)〗^{2} +(-8)\\

128- 16- 56 = 64- 8\\

56 = 56\\

   

2*(7)^{2} + 2*7 - 56 =(7)^{2} + 7\\

98+ 14 - 56 =49 + 7\\

98+ 14 - 56 =49 + 7\\

56 =56\\

x^{2} -9x= x- 9\\

x^{2} -9x= x- 9\\

x^2-x-9x+9=0

x^2-10x+9=0

x_1,2  =  (-b ± √(b^2-4 ac))/2a

                                                                       a = 1, b = -10, c = 9

x_1,2  =  (-(-10) ± √(〖(-10)〗^2-4* 1*9))/(2*1)

x_1  =  (10-8)/2=1

x_2  =  (10+8)/2=9

Proof

x^{2} -9x= x- 9\\

1^{2} -9*1= 1- 9\\

-8= - 8\\

9^{2} -9*9= 9- 9\\

0= 0\\